Twitter and ideology in the 2018 presidential elections - Iasulaitis, Sylvia (2022)
Social networking sites have been widely used in electoral campaigns, especially Twitter. This article aims to comparatively analyze the ideological campaign strategies by Twitter in the 2018 elections in Brazil. To achieve this purpose, data mining strategies were used via the Twitter API with the Python programming language, through the Tweepy library. A corpus composed of all tweets (n=3182) mined from the official accounts of the main presidential candidates during the electoral race was categorized and analyzed based on the content analysis technique. With the empirical study presented, it is expected to contribute to the specialized literature due to the application of an already classic international methodology (MRG/Manifesto Project) in its most recent version to a new unit of analysis: the mined content of social media platforms and websites of digital social networks, which are new tools available to candidates to communicate their programmatic and ideological messages to voters.